2016
DOI: 10.1002/spe.2400
|View full text |Cite
|
Sign up to set email alerts
|

Reliable self-deployment of distributed cloud applications

Abstract: SUMMARYCloud applications consist of a set of interconnected software elements distributed over several virtual machines, themselves hosted on remote physical servers. Most existing solutions for deploying such applications require human intervention to configure parts of the system, do not conform to functional dependencies among elements that must be respected when starting them, and do not handle virtual machine failures that can occur when deploying an application. This paper presents a self-deployment pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…They also propose several kinds of analysis for checking, e.g., the validity of a management plan or the possibility to reach a certain configuration given a plan. [37] presents a self-deployment protocol that aims at configuring a set of software components distributed over a set of virtual machines. This protocol works in a fully automated and decentralized way while supporting VM failures.…”
Section: Composition (Techniques)mentioning
confidence: 99%
“…They also propose several kinds of analysis for checking, e.g., the validity of a management plan or the possibility to reach a certain configuration given a plan. [37] presents a self-deployment protocol that aims at configuring a set of software components distributed over a set of virtual machines. This protocol works in a fully automated and decentralized way while supporting VM failures.…”
Section: Composition (Techniques)mentioning
confidence: 99%
“…This protocol supports virtual machine and network failures, and always succeeds in deploying an application when faced with a finite number of failures. The main difference with our work is that [11] considers stateless applications whereas we focus on consistent state recovery, and consequently the state of the application needs to be stored.…”
Section: Fault-tolerant Management Systemsmentioning
confidence: 99%
“…One of the big advantages of an agent‐based approach is the reliability and resiliency against failures as shown by Xavier et al and Kirschnick et al Lavinal et al have shown that the local autonomy of each agent combined with their organizing behavior enables global management autonomy in a distributed environment. The flexibility of the agent‐based approach allows it to manage not only analytical platforms but also the workloads running on top of those platforms as shown by the authors' previous work .…”
Section: Related Workmentioning
confidence: 99%